Stress-Based High-Throughput Screening Assays to Identify Inhibitors of Cell Envelope Biogenesis - Steenhuis, Maurice (Antibiotics (Basel), 2020)
The structural integrity of the Gram-negative cell envelope is guarded by several stress responses, such as the σ(E), Cpx and Rcs systems. Here, we report on assays that monitor these responses in E. coli upon addition of antibacterial compounds. Interestingly, compromised peptidoglycan synthesis, outer membrane biogenesis and LPS integrity predominantly activated the Rcs response, which we developed into a robust HTS (high-throughput screening) assay that is suited for phenotypic compound screening. Furthermore, by interrogating all three cell envelope stress reporters, and a reporter for the cytosolic heat-shock response as control, we found that inhibitors of specific envelope targets induce stress reporter profiles that are distinct in quality, amplitude and kinetics. Finally, we show that by using a host strain with a more permeable outer membrane, large-scaffold antibiotics can also be identified by the reporter assays. Together, the data suggest that stress profiling is a useful first filter for HTS aimed at inhibitors of cell envelope processes.